EFFECT OF ENSILING TIME ON THE QUALITY OF BANANA PEELINGS AND PEA Pon SILAGE (Biological Sciences - PJSIR, 2021)
Si lage was prepared from banana peeli ngs (BP) as such (100%), BP + Lactobacillus , BP (with 70% moi sture), BP 70% , moisture + Lactobacillus, BP (50%) + pea pod (PP) 50%, BP (50%) +  PP  (50%)  +  Lactobacillus , PP  (70%  moisture)  +  Lactobacillus  and  PP  with   70%  moisture  by  mixing  them  and  packed  in  pla stic  bags  at  ambient  temperature  (28-35  °C) for 60  days  of  fennentation .   Dry  matter  and  protein  contents  showed  gradual  increase  du ring  the  ensili ng period.